An ultra-low bandgap diketopyrrolopyrrole (DPP)-based polymer with balanced ambipolar charge transport for organic field-effect transistors. Issue 82 (18th August 2016) - Jiang, Tao; Xue, Zhongyuan; Ford, Michael; Shaw, Jessica; Cao, Xudong; Tao, Youtian; Hu, Yuanyuan; Huang, Wei
Abstract : Molecular design on new A1 –A2 type polymer pDTDPP–TTF exhibiting ultra-low bandgap and balanced ambipolar charge transport was conducted for solution-processed OFETs. Abstract : A new A1 –A2 type polymer pDTDPP–TTF containing diketopyrrolopyrrole (DPP) and 2-ethylhexyl-3-fluorothieno[3, 4- b ]thiophene-2-carboxylate (TTF) as the main electron-accepting building blocks has been synthesized via Suzuki cross-coupling polycondensation. The introduction of TTF as an additional electron-deficient unit significantly lowers the LUMO energy level of this DPP containing polymer to −4.37 eV which is beneficial for efficient electron injection and transport. The pDTDPP–TTF polymer shows an ultra narrow optical bandgap of 1.06 eV with a broad absorption spectra covering the visible to near infrared region of up to 1300 nm. Solution-processed OFET devices with pDTDPP–TTF as the active semiconducting layer have been fabricated with the configurations of both bottom-gate bottom-contact (BG–BC) and top-gate bottom-contact (TG–BC). The BG–BC devices with SiO2 as a dielectric exhibit ambipolar behavior with a hole and electron mobility of 1.85 × 10 −4 and 3.55 × 10 −5 cm 2 V −1 s −1, respectively. Improved OFET performance has been achieved in TG–BC devices by using PMMA as the dielectric; balanced ambipolar charge transport is obtained with a hole and electron mobility of 6.17 × 10 −3 cm 2 V −1 s −1 and 3.13 × 10 −3 cm 2 V −1 s −1, respectively. To the best of our knowledge, our work is among the very few examples of ultra-low bandgap semiconducting polymers with balanced ambipolar charge transport properties.